2002
DOI: 10.1080/00288233.2002.9513519
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in the ability ofMicroctonus aethiopoides(Hymenoptera: Braconidae) to parasitiseSitona lepidus(Coleoptera: Curculionidae)

Abstract: Sitona discoideus (Coleoptera: Curculionidae), a pest of lucerne (Medicago sativa), is controlled in New Zealand by the introduced parasitoid Microctonus aethiopoides (Hymenoptera: Braconidae). Unfortunately, a second Sitona species, S. lepidus (=flavescens), which has recently invaded New Zealand and has become a pest of white clover (Trifolium repens), is not parasitised by M. aethiopoides. Previous experiments have shown that New Zealand M. aethiopoides will attack S. lepidus, but its eggs appear to be kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The M. aethiopoides collected were able to be continuously laboratory-reared on New Zealand as well as British-sourced populations of S. lepidus. This contrasted with an inability to rear New Zealand M. aethiopoides on New Zealand S. lepidus (Barratt et al 1997) and was consistent with the results of Phillips et al (2002) who demonstrated genetic differentiation between French and New Zealand M. aethiopoides, while finding no difference in host suitability for French M. aethiopoides parasitising French and New Zealand S. lepidus. The different geographical populations of M. aethiopoides were forwarded to New Zealand containment facilities where efforts have continued to maintain genetic diversity (Goldson et al 2001).…”
Section: Parasitoid Recoverysupporting
confidence: 87%
See 1 more Smart Citation
“…The M. aethiopoides collected were able to be continuously laboratory-reared on New Zealand as well as British-sourced populations of S. lepidus. This contrasted with an inability to rear New Zealand M. aethiopoides on New Zealand S. lepidus (Barratt et al 1997) and was consistent with the results of Phillips et al (2002) who demonstrated genetic differentiation between French and New Zealand M. aethiopoides, while finding no difference in host suitability for French M. aethiopoides parasitising French and New Zealand S. lepidus. The different geographical populations of M. aethiopoides were forwarded to New Zealand containment facilities where efforts have continued to maintain genetic diversity (Goldson et al 2001).…”
Section: Parasitoid Recoverysupporting
confidence: 87%
“…Both are solitary endoparasitoids attacking the adult weevil, and there was initial hope that these parasitoids could be useful in suppressing S. lepidus. However, subsequent experimentation demonstrated that M. aethiopoides and M. hyperodae were ineffective as parasites of New Zealand populations of S. lepidus (Barratt et al 1997); a conclusion further supported by the research of Phillips et al (2002). Consequently, in 1998, a search for suitable agents was commenced in the United States and Europe.…”
Section: Introductionmentioning
confidence: 98%
“…In insects, ISSR markers have been employed to characterize different lineages in Bombyx mori [23] and Antheraea mylitta [24], as well as in studies on hybridization [25], genetic diversity [26][28], and conservation genetics [29].…”
Section: Introductionmentioning
confidence: 99%
“…so it is not possible to deduce anything about genetic diVerences based on VLPs. Using ampliWcation of inter simple sequence repeat (ISSR) regions of M. aethiopoides DNA, Phillips et al (2002) showed that the degree of genetic diVerentiation between Moroccan and European M. aethiopoides was insuYcient to infer diVerentiation to the extent of species or subspecies. Iline and Phillips (2003) examined allozyme variation between Moroccan and European M. aethiopoides specimens, and of nine enzyme systems and 11 general proteins, only esterase (known to be amongst the most variable of enzmes) was polymorphic in this comparison.…”
Section: Discussionmentioning
confidence: 99%